The effect of artificial tear administration on visual field testing in patients with glaucoma and dry eye - ŞAHİN, ÖZLEM (NATURE PUBLISHING GROUP, 2007)
Aim: To examine the effects of artificial tear administration on perimetry of primary open-angle glaucoma patients with dry eye. Methods: A total of 40 patients with primary open-angle glaucoma experienced in automated perimetry with symptoms of dry eye were enrolled in this study. After their pretest visit, they were instructed to use artificial tear four times a day in both eyes for 1 week. After 1 week, patients had visual field testing. Test taking time, reliability parameters (false-positive and false-negative errors) visual field indices and number of depressed points at different probability levels (P < 5%, P < 2%, P < 1%, P < 0.5%) in both total and pattern deviation plots were compared using paired T test. Results: We found significant improvement in reliability parameters (false-positive errors from 2.4 +/- 2.1 to 2.1 +/- 1.9, P = 0.02; and false-negative errors from 7.3 +/- 6.4 to 4.8 +/- 3.6, P = 0.01) and visual field indices (MD increased from 5.97 +/- 5.61 to 4.57 +/- 4.53, P = 0.001; PSD from 4.67 +/- 2.95 to 4.13 +/- 2.77, P = 0.04 and SF decreased from 2.24 +/- 1.23 to 1.83 +/- 0.77, P = 0.04) in the second testing after artificial tear administration. Test time significantly increased from 11.66 +/- 2.55 min to 14.26 +/- 1.36, P = 0.001. The number of depressed points at probability levels P < 1% (P = 0.03) and P < 0.5% (P = 0.04) at total deviation plot and Po2% (P = 0.02) and P < 0.5% (P = 0.009) in pattern deviation plot decreased significantly. Conclusion: Artificial tear administration in glaucomatous patients with dry eye seems to improve significantly reliability parameters and visual field indices.
Keywords: glaucoma; visual field; dry eye; artificial tears; PERIMETRIC EXPERIENCE; AUTOMATED PERIMETRY; OCULAR SURFACE; TOPICAL DRUGS; PREVALENCE; MEDICATION; THRESHOLD; SYMPTOMS; SIGNS